Resiliensi pada Ibu Berperan Ganda: Peran Jumlah Anak dan Lama Pernikahan - Yulian Sri Lestari; Andi Muthiasari Handayani; Jusmiati; Abdul Manab; Rizqa Sabrina Badjarad (Yayasan Azhar Amanaa Yogyakarta, 2025)
Resilience is a critical psychological resource that enables working mothers with dual roles to cope effectively with the demands of work and family life. However, family-related factors contributing to resilience remain underexplored. This study examined the effects of marriage duration and number of children on the resilience of working mothers with dual roles. A quantitative cross-sectional survey design was employed involving 321 married working mothers with children selected through purposive sampling. Data were collected using a resilience scale and analyzed using simple and multiple regression analyses with SPSS. The findings revealed that marriage duration had a positive and significant effect on resilience (β = 0.146, p = 0.009), whereas the number of children had no significant effect (β = 0.054, p = 0.336). Simultaneously, marriage duration and number of children significantly predicted resilience (F = 3.708, p = 0.026), although only marriage duration remained a consistent predictor in the regression model. These findings suggest that resilience among working mothers is shaped more by adaptive experiences accumulated throughout married life than by demographic characteristics such as the number of children. The study highlights the importance of strengthening family resources, spousal support, and family-friendly workplace policies to enhance resilience among working mothers.